Factors influencing success of cement versus screw-retained implant restorations: a clinical review - Ahmad Manawar; B. Dhanasekar; I. N. Aparna; Hina Naim (Ariesdue, 2012)
Aim: As more and more dental practitioners are focusing on implant-supported fixed restorations, some clinicians favor the use of cement retained restorations while others consider screw retained prosthesis to be the best choice. Discussion: In screw-retained restorations, the fastening screw provides a solid joint between the restoration and the implant abutment, while in cement-retained prostheses the restorative screw is eliminated to enhance esthetics, occlusal stability, and passive fit of the restorations. The factors that influence the type of fixation of the prostheses to the implants like passivity of the framework, ease of fabrication, occlusion, esthetics, accessibility, retention and retrievability are discussed in this article with scientific studies demonstrating superior outcomes of one technique over another. Screwretained implant restorations have an advantage of predictable retention, retrievability and lack of potentially retained subgingival cement. However, a few disadvantages exist such as precise placement of the implant for optimal and esthetic location of the screw access hole and obtaining passive fit. On the other hand, cement retained restorations eliminate unesthetic screw access holes, have passive fit of castings, reduced complexity of clinical and lab procedures, enhanced esthetics, reduced cost factors and non disrupted morphology of the occlusal table. Conclusion: This article compares the advantages, potential disadvantages and limitations of screw and cement retained restorations and their specific implications in the most common clinical situation.